Favorite Photo Spot for Models of Tourist Destinations and Trends for Tourist Selfies in Special Region of Yogyakarta - Yulianto, Atun; Brahmanto, Erlangga (Jurnal Penelitian Pariwisata, 2023)
The growth in the number of tourists to the Special Region of Yogyakarta by students or the current millennial generation is an opportunity for managers of tourist destinations to develop visual spaces that support tourists' desire to take selfies. The purpose of this study is to find out which photo spot models are most in demand by tourists. This study employs a qualitative descriptive method supplemented by a survey, with the photo spot model serving as the research object and a quota sample of 100 tourists who have visited Yogyakarta's Special Region. Data collection system for sampling using a simple random sampling method and polling technique. The results of this study are tourist interest in photo spots that combine nature and man-made in an outdoor tourist destination that has a mountainous landscape and cultural customs of the local community with their distinctive traditions. Keywords: Photo Spots, Selfies, Tourist Destinations